STUDY OF CARBON DIOXIDE ADSORPTION ON NANOPOROUS ACTIVATED CARBON FIXED-BED USING COMPUTATIONAL APPROACH - ZOHAIR, SYED ALI QASIM (2015)
Natural gas is a mixture of methane and some other gases that are actually impurities. CO2 is considered as a major impurity and an undesirable component that needs to be removed. Various separation processes are used in the industry for its removal and adsorption using packed bed is a promising technology for CO2 capture. Based on regeneration methods, packed bed adsorption utilizes Thermal swing adsorption (TSA), Vacuum swing adsorption (VSA), Pressure swing adsorption (PSA) and Electric swing adsorption (ESA). In this work, adsorption process for the gas mixture is simulated inside packed-bed nanoporous media through Computational Fluid Dynamics (CFD) approach. Activated carbon is used as an adsorbent to capture C02. Simulations are performed in a CFD software ANSYS FLUENT® 14. The three dimensional model used in the simulation for adsorption takes into account the equilibrium and kinetic properties.